Zimbabwe : Technical Assistance Report-Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
In response to a request from the Reserve Bank of Zimbabwe (RBZ), and with the support of the International Monetary Fund's (IMF's) African Department (AFR), a monetary and financial statistics (MFS) technical assistance mission visited Harare, Zimbabwe, during October 16-27, 2017. The mission's main objective was to assist the RBZ in finalizing its work of compiling MFS of the Central Bank (CB) and Other Depository Corporations (ODCs) in accordance with the Monetary and Financial Statistics Manual and Compilation Guide (MFSMCG). Compilation of these data will lead to the regular reporting of improved monetary data for publication in International Financial Statistics (IFS) and provide MFS data for use by the IMF African Department (AFR) and the Reserve Bank of Zimbabwe in their research and publications.